Effects of different dehydration methods on the color, nutritional, and functional characteristics of okara - SILVEIRA, Bruna Méris Grigoleto da; BERMEJO-POZA, Rubén; VÁZQUEZ, Jesús de la Fuente; RAMIRES, Thiago Gentil; PONSANO, Elisa Helena Giglio (Food Science and Technology, 2025)
Okara, a by-product of soybean (Glycine max L.) processing, is rich in nutrients, including proteins, fibers, lipids, minerals, and bioactive compounds. However, its high moisture content (70–80%) makes it susceptible to spoilage. This study investigated the effects of four drying methods (using equipment such as a conventional electric oven, a microwave oven, a forced air convection oven, and a homemade dehydrator) on the color, microbiological safety, nutritional composition, percentage yield, and technological properties of dehydrated okaras. The following analyses were performed: yield, microbiological (Escherichia coli and Salmonella sp.,) characteristics, proximate composition, fatty acid profile, La*b* color, water absorption index (WAI), oil absorption index (OAI), and emulsifying activity (EA). No pathogenic microorganisms were detected. Microwave drying resulted in the lowest yield (4.2%) but produced the highest protein concentration (38.4%), making it ideal for enhancing the nutritional value of food products. Conventional oven and microwave drying showed the highest EA (47.1% and 46.5%, respectively), indicating their suitability for emulsified product applications. Conversely, homemade dehydrator was suitable for gel and bakery product formulations (WAI, 6.2%). Additionally, homemade dehydrator caused minimal color changes (L, 78.4; a*, 4.5; b*, 25.0), making it preferable for applications in which the color retention in okara-enriched food products is crucial.